Signaling pathways regulated by natural active ingredients in the fight against exercise fatigue-a review - Zhao, Rongyue; Wu, Ruomeng; Jin, Junjie; Ning, Ke; Wang, Zhuo; Yi, Xuejie; Kapilevich, Leonid; Liu, Jiao (Frontiers in Pharmacology, 2023)
Exercise fatigue is a normal protective mechanism of the body. However, long-term fatigue hinders normal metabolism and exercise capacity. The generation and recovery from exercise fatigue involves alterations in multiple signaling pathways, mainly AMPK, PI3K/Akt, Nrf2/ARE, NF-κB, PINK1/Parkin, and BDNF/TrkB, as well as MAPK signaling pathways that mediate energy supply, reduction of metabolites, oxidative stress homeostasis, muscle fiber type switching, and central protective effects. In recent studies, a rich variety of natural active ingredients have been identified in traditional Chinese medicines and plant extracts with anti-fatigue effects, opening up the field of research in new anti-fatigue drugs. In this review we give an overview of the signaling pathways associated with the activity of natural food active ingredients against exercise fatigue. Such a comprehensive review is necessary to understand the potential of these materials as preventive measures and treatments of exercise fatigue. We expect the findings highlighted and discussed here will help guide the development of new health products and provide a theoretical and scientific basis for future research on exercise fatigue.